Public perceptions, knowledge, responsibilities, and behavior intentions on marine litter: Identifying profiles of small oceanic islands inhabitants - Bettencourt, Sara (2023)
Marine litter is a global threat, particularly on oceanic islands where the problem is exacerbated. Perceptions, knowledge, awareness, and attitudes towards the theme are crucial in its mitigation and prevention. This study assessed these points through a questionnaire to the inhabitants of a Portuguese archipelago. Data revealed that people associate marine litter with plastic and its impacts and are well informed about its sources and pathways. Yet, the degradation rates of marine items were frequently underestimated and the problem of marine litter was attributed, among others, to littering, single-use products, and excessive packaging. Some individuals did not consider themselves responsible for reducing marine litter, attributing responsibilities to third parties. The youngest group, men, and students were the ones who reported less litter-reducing intentions and behaviors. Distinct profiles were traced using the questionnaire’s answers, highlighting who needs marine litter literacy. Individuals who do not consider marine litter a current threat and live in a community that does not care about marine litter (profiles 1 and 2) were the groups that needed deeper intervention, due to their low perception and understanding of the problem. Marine litter literacy, management, and governance measures are necessary so that the public recognizes marine litter as a current threat, is worried about its impacts, avoids plastic use, and choses re-useable products (profile 4). In the studied oceanic islands, results indicated marine litter is not fully perceived by the public. A global and transformative shift in the way people are educated and behave towards waste and pollution is required, thereby highlighting the importance of increasing public perceptions assessment and marine litter literacy in the society.